Surgical Management of a Completely Avulsed Adductor Longus Muscle in a Professional Equestrian Rider - Conal Quah; Andrew Cottam; James Hutchinson (Case Reports in Orthopedics)
Avulsion injuries of the adductor longus muscle tendon are rare and a challenge to manage especially in athletes. There has been little published literature on the outcome of conservative and operative treatment for these injuries. We report the first case of an acute adductor longus avulsion injury which was surgically repaired in a professional equestrian rider. Return to full preinjury function was achieved at 3 months with surgical repair using 3 suture anchors.